Seismic Behaviour of Cast-In-Situ Phosphogypsum-Reinforced Concrete Grid Frame Composite Walls - Qin Wu; Huagang Zhang; Hongniao Chen; Xin Zhang; YanHui Wei; Li Li; Kejian Ma (Advances in Civil Engineering)
This paper mainly studies the effect of cast-in-situ phosphogypsum on seismic behaviour of reinforced concrete grid frame. The mechanical behaviour of three reinforced concrete grid frames and four cast-in-situ phosphogypsum-reinforced concrete grid frame composite walls under low cycle alternating load was designed and tested. The test results show that the reinforced concrete grid frame has less bearing capacity and poor energy consumption. The addition of cast-in-situ phosphogypsum can effectively improve the seismic behaviour of the reinforced concrete grid frame. Compared with the reinforced concrete grid frame, the bearing capacity of the cast-in-situ phosphogypsum-reinforced concrete grid frame composite wall is increased by 2-3 times, the displacement ductility coefficient is increased by 0.95∼1.2 times, and the relative accumulative energy consumption is increased by 86%∼216%. This shows that the composite wall has better bearing capacity, ductility, and energy dissipation capacity.